Exploring determinants of purchase intent for chinese steel and iron goods in Batam - Kesumahati, Erilia; Fernado, Fernado (Center for Economics, Business and Entrepreneurship Development Faculty of Economics and Business, Universitas Muhammadiyah Malang, 2024)
This study aims to investigate the underlying reasons behind the heightened purchase inclination towards imported Chinese steel and iron products within Batam City. Given that iron and steel products emerged as one of the most extensively imported categories in 2020, they serve as the primary focus of this research. Data collection was conducted through Google Forms, completed by 211 building shop owners or managers. Analysis was carried out utilizing SPSS version 26.0.0, encompassing data quality assessment, classical assumption testing, and multiple linear analysis. The findings reveal that subjective norms and perceived behavioral control significantly and positively influence the purchase intention of Chinese steel and iron products.